Understanding social vulnerability to climate change using a ‘riskscapes’ lens: case studies from Ethiopia and Tanzania - Gebreyes, Million; Theodory, Theobald (ERDKUNDE, 2018)
This paper uses the concept of riskscapes to understand the way climate risks manifest themselves and interact with other risks to create vulnerable local communities in Ethiopia and Tanzania. The main research question we addressed is: what are the different sources of risks facing farmers’ livelihoods in the selected case study areas of both countries and where does climate risk fit? The study uses qualitative research methodology with thick description of our case studies to identify variables which are common in both countries. Accordingly, we identified six major risk settings which are important in determining the vulnerability of communities, namely ‘climate hazard risk setting’, ‘subsistence risk setting’, ‘population increase risk setting’, ‘state policy failure risk setting’, ‘market volatility risk setting’, and ‘supernatural risk setting’. Our findings highlight two important points. First, the interaction between risk settings and climate risks differs from one place to another, depending on the ecological endowment and social fabric of the area of interest. Second, local communities and experts attach different importance to the six risk settings identified and the interaction between them, making up local community and expert riskscapes. Hence, we argue that effective climate risk management in the context of sub-Saharan Africa requires proper understanding of the way various risk settings interact with climate risk, and of the different weight that relevant actors attribute to these risks and their interaction.